UTILIZATION OF PINEAPPLE PROCESSING LIQUID WASTE IN BIODEGRADATION OF DISPOSABLE FACE MASK BY BACTERIA FROM LAMPUNG BAY - Deviany, Deviany; Zhofiroh, Nawrah Meisyah Muthi'ah; Febrina, Yane Fita; Yusuf, Reggina Aulia; Achmad, Feerzet; Yuniarti, Reni; Istiadi, Khaerunissa Anbar (BRIN - Badan Riset dan Inovasi Nasional, 2024)
The designation of COVID-19 as a global pandemic led to an increased use of single-use face masks, which result in waste that is difficult to degrade and has the potential to release microplastic fibers into the environment. This study aims to examine the im-pact of adding pineapple peel liquid waste (LCN) as a growth medium for the biodeg-radation of single-use face masks by bacterial isolates obtained from the waters of the Lampung Bay. The study investigates how LCN affects the efficiency of mask degra-dation by microorganisms, as well as how the ratio of LCN mixed with other growth media, such as Nutrient Broth (NB), influences the degradation process. The biodeg-radation process was carried out using a biostimulation technique, where bacterial iso-lates were incubated in media containing LCN at a 1:1 ratio. The degradation process lasted for 15 days, with the results being analyzed using gravimetry and Fourier-Transform Infrared Spectroscopy (FTIR). Gravimetric results showed a greater weight reduction in treated masks compared to the control masks. FTIR analysis also indicat-ed changes in the intensity of functional groups in the degraded layers of the masks, as well as the emergence of C≡C functional groups in the second and third layers. This study demonstrates that the addition of LCN can accelerate the biodegradation of sin-gle-use face masks, offering a new approach for managing mask waste.